Przekład europejskiego nakazu aresztowania w świetle komunikacji interkulturowej - Bednarek, Grażyna (Investigationes Linguisticae, 2009)
The aim of this paper is to examine translation of the European arrest warrant in the light of intercultural communication. The paper consists of three parts. The first part addresses major aspects of judicial cooperation in criminal matters within the territory of the European Union (EU) and introduces the European arrest warrant (EAW) as one of the major legal instruments of such cooperation. The second part focuses on the notion of legal translation as an act of intercultural communication. The third part illustrates, via translation of the European arrest warrant, how certain differences between the two most important legal families of the world, the Common Law and the Civil Law, influence the process of intercultural communication.